Shaking table test of comparison and optimization of seismic performance of slope reinforcement with multi-anchor piles. Issue 145 (June 2021) - Pai, Li fang; Wu, Hong gang
Abstract: We carried out a shaking table test on a slope model reinforced by multi-anchor piles. By analyzing the characteristics of acceleration in time domain, we obtained the spatial position variation characteristics of acceleration particles represented by peak acceleration ratio ( R a ) and motion duration ( B du ). Based on Fourier variation and statistical probability scatter matrix, we proposed the damage level correlation quantitatively characterized by the spectral characteristics of acceleration. Then the potential deformation and failure potential displacement parameters ( P d ) of ground motion were calculated by Spectra Response Analysis (SPECTR), and regional differences of multi-anchor pile reinforcement were obtained by combining slope model stability analysis. We analyzed that R a and B du mainly reflected the zonal variation along the pile elevation under different earthquake intensities. The ratio of Peak Ground Velocity (PGV) to Peak Ground Acceleration (PGV/PGA) had a correlation with the peak input energy of ground motion. Seismic waves in low frequency band (≤10 Hz) had great influence on the structure. Pile sliding surface P d value was large, which was easy to become the weak link of earthquake resistance of multi-anchor piles. The optimized multi-anchor piles acted as a buffer and energy dissipation for the deformation of the slope body under rarely occurred earthquake. The optimization effect was related to the position of the shock absorption layer. These results were helpful for us to provide theoretical basis for the optimal seismic design of multi-anchor piles. Highlights: We conducted a shaking table test on the slope reinforced by multi-anchor piles. The research records the acceleration dynamic response and post-test behavior of multi-anchor pile optimization or not. We obtained the characteristics of spatial position of the multi-anchor pile acceleration particles characterized. We obtained the magnitude correlation of quantitatively characterizing the damage level of slope reinforced. We obtained the regional difference of the displacement parameter P d of the multi-anchor point pile slope model.